The Impact of Environmental Management on Firm Performance - Klassen, Robert D.; McLaughlin, Curtis P. (Management Science, 1996)
Environmental management has the potential to play a pivotal role in the financial performance of the firm. Many individuals suggest that profitability is hurt by the higher production costs of environmental management initiatives, while others cite anecdotal evidence of increased profitability. A theoretical model is proposed that links strong environmental management to improved perceived future financial performance, as measured by stock market performance. The linkage to firm performance is tested empirically using financial event methodology and archival data of firm-level environmental and financial performance. Significant positive returns were measured for strong environmental management as indicated by environmental performance awards, and significant negative returns were measured for weak environmental management as indicated by environmental crises. The implicit financial market valuation of these events also was estimated. Cross-sectional analysis of the environmental award events revealed differences for first-time awards and between industries. First-time award announcements were associated with greater increases in market valuation, although smaller increases were observed for firms in environmentally dirty industries, possibly indicative of market skepticism. This linkage between environmental management and financial performance can be used by both researchers and practitioners as one measure of the benefits experienced by industry leaders, and as one criterion against which to measure investment alternatives.